2019
DOI: 10.5380/abclima.v25i0.69421
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologia, Fatores Climáticas E Distribuição Espacial Da Dengue Em Uma Capital Do Nordeste Do Brasil

Abstract: Objetivo: Avaliar correlação de parâmetros meteorológicos com a incidência de Dengue em Maceió-AL, Brasil, e descrever a distribuição espacial e perfil. Métodos: Foram considerados os registros de casos novos de 01/01/2010 a 31/12/2016. A incidência foi verificada por de Taxa Anual Média de Incidência (TAM) através da abordagem bayesiana. A correlação de Pearson foi utilizada para avaliar a relação entre fatores climáticos e incidência de casos. A espacialização foi realizada por meio da geração de mapas temát… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
1
1
Order By: Relevance
“…These climatic correlations were not statistically significant (P > 0.05). Some studies carried out in northeastern, southeastern and northern Brazil and abroad 16,18,19,20 have shown correlations contrary to those of the present study, given that they reported associations between climatic factors and the incidence of dengue. On the other hand, some other studies 28,29 have confirmed the lack of correlation of climatic factors with the incidence of dengue.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These climatic correlations were not statistically significant (P > 0.05). Some studies carried out in northeastern, southeastern and northern Brazil and abroad 16,18,19,20 have shown correlations contrary to those of the present study, given that they reported associations between climatic factors and the incidence of dengue. On the other hand, some other studies 28,29 have confirmed the lack of correlation of climatic factors with the incidence of dengue.…”
Section: Discussioncontrasting
confidence: 99%
“…It showed that precipitation and humidity influenced the epidemiology of dengue. 20 A study carried out in Pakistan showed that the incidence of the disease was influenced by climatic factors, such that the transmission rates among mosquitoes were higher within a favorable temperature range from 28 °C to 32 °C. 21 Laboratory data on larval development of Aedes aegypti have confirmed that these temperatures favor multiplication of these larvae, consequently enabling greater production of vectors and producing increased incidence of dengue.…”
Section: Discussionmentioning
confidence: 99%
“…No âmbito da COVID-19, no Brasil, essas tecnologias podem auxiliar os estados e municípios no mapeamento da situação de regiões, cidades e estados, facilitando as avaliações das medidas tomadas para combater a pandemia até o momento e também as futuras. Esses trabalhos facilitam as ações das secretarias de saúde, principalmente nas medidas de prevenção através do isolamento social (SANTOS JÚNIOR;SILVA, 2019;CABRAL et al, 2020).…”
Section: Resultsunclassified
“…It is worth mentioning that the mosquito has great urban adaptability, they need reservoirs of water, preferably clean, to lay their eggs, hence the importance of rainfall and maintenance of high temperature for their development. Maceió, capital of Alagoas (AL) located on the ENEB coast, stands out, with a history of dengue occurrence (Santos-Jr & Silva, 2019; and therefore needs monitoring and follow-up by public managers.…”
Section: Introductionmentioning
confidence: 99%